Selecting drug formulation for the treatment and prevention of retinal disorders - O.V. Filippova (РМЖ "Клиническая офтальмология")
O.V. Filippova Sechenov University, Moscow, Russian Federation Retinal disorders are common in ophthalmic patients. Among them, age-related macular degeneration (AMD) leads to significant visual impairment and irreversible blindness in millions of patients worldwide. The causes and pathogenesis of AMD remain elusive, however, xanthophylls, i.e., lutein and zeaxanthin, are known to provide benefits in terms of the prevention and treatment for early AMD. AMD treatment is challenging due to the difficulties in selecting agents to improve retinal metabolism and developing optimal drug formulation as well as their administration routes. Blood-ocular barrier prevents many pharmaceuticals from entering posterior eye segment, in particular, the retina. Peroral medications are certainly more comfortable for patients, however, they do not always provide penetration through the blood-ocular barrier. Modalities to improve drug efficacy by using various formulations, in particular, modern technologies (i.e., sustained-release drug delivery systems)  are discussed. Among them, Ocuvite forte contains lutein and zeaxanthin microcapsules which provide controlled release delivery of active substances thus maintaining stable blood concentrations of lutein and zeaxanthin entering the retina. Keywords: retina, age-related macular degeneration, antioxidants, lutein, zeaxanthin, bioavailability, microcapsules, Ocuvite forte. For citation: Filippova O.V. Selecting drug formulation for the treatment and prevention of retinal disorders. Russian Journal of Clinical Ophthalmology. 2019;19(4):211–216.